2021
DOI: 10.1029/2020ja028726
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ICON‐MIGHTI Thermospheric Wind Observations: 1. Nighttime Red‐Line Ground‐Based Fabry‐Perot Interferometers

Abstract: Observations of the nighttime thermospheric wind from two ground‐based Fabry‐Perot Interferometers are compared to the level 2.1 and 2.2 data products from the Michelson Interferometer Global High‐resolution Thermospheric Imaging (MIGHTI) onboard National Aeronautics and Space Administration's Ionospheric Connection Explorer to assess and validate the methodology used to generate measurements of neutral thermospheric winds observed by MIGHTI. We find generally good agreement between observations approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 48 publications
2
55
0
Order By: Relevance
“…New observations of thermosphere winds on a global scale are presently coming from the NASA Ionospheric Connection Explorer (ICON) (Immel et al, 2018). ICON is equipped with a Michelson interferometer, built by the NRL, that measures winds and temperatures in the altitude range 90-300 km (Harding et al, 2021;Makela et al, 2021). We are hopeful that newly accurate thermosphere now-casting data products might be developed.…”
Section: Discussion: Can These Effects Be Forecasted?mentioning
confidence: 99%
“…New observations of thermosphere winds on a global scale are presently coming from the NASA Ionospheric Connection Explorer (ICON) (Immel et al, 2018). ICON is equipped with a Michelson interferometer, built by the NRL, that measures winds and temperatures in the altitude range 90-300 km (Harding et al, 2021;Makela et al, 2021). We are hopeful that newly accurate thermosphere now-casting data products might be developed.…”
Section: Discussion: Can These Effects Be Forecasted?mentioning
confidence: 99%
“…The total ion densities are considered equivalent to electron densities, and are hereafter referred to as Ne. The winds are measured to a precision of order 1.2–4.7 ms −1 (Harding et al., 2017), and have been validated against G‐B measurements (Harding et al., 2021; Makela et al., 2021). The drift measurements are accurate to 7.5 ms −1 whenever O + densities are greater than 10 4 cm −3 (Heelis et al., 2017); this condition is met for all data analyzed here.…”
Section: Methodsmentioning
confidence: 99%
“…The total ion densities are considered equivalent to electron densities, and are hereafter referred to as Ne. The winds are measured to a precision of order 1.2-4.7 ms −1 (Harding et al, 2017), and have been validated against G-B measurements (Harding et al, 2021;Makela et al, 2021).…”
Section: Icon Neutral Wind Ion Drift and Density Measurementsmentioning
confidence: 99%
“…Recent validation studies for ICON-MIGHTI thermospheric winds conducted using ground-based Fabry-Pérot Interferometers Makela et al [51] and specular meteor radars Harding et al [52] have demonstrated the utility of ICON winds for comparison with ground-based or ship-borne measurements.…”
Section: Icon Satellitementioning
confidence: 99%